Breastfeeding is associated with lower subclinical atherosclerosis in postmenopausal women. (1st September 2020) - Augoulea, Areti; Armeni, Eleni; Paschou, Stavroula A.; Georgiopoulos, Georgios; Stamatelopoulos, Kimon; Lambrinoudaki, Irene
Abstract: Objective: To evaluate the association between a personal history of lactation and indices of subclinical atherosclerosis in postmenopausal women. Methods: We evaluated the association between a history of breastfeeding and indices of subclinical atherosclerosis (pulse wave velocity, PWV; intima-media thickness [IMT]; atherosclerotic plaque presence) in 197 parous postmenopausal women with history of breastfeeding. Results: Women who reported breastfeeding ≥6 months when compared with women who reported breastfeeding for 1–5 months exhibited significantly lower values of common carotid artery IMT (Model R 2 =15.7%, b-coefficient = −0.170, 95% CI: −0.208—0.001, p -value = .019) and lower odds of subclinical atherosclerosis (Model X 2 =28.127, OR = 0.491, 95% CI 0.318–0.999, p -value = .049), adjusting for traditional cardiovascular risk factors. Conclusions: Postmenopausal women with a history of breastfeeding for at least 6 months have a lower prevalence of subclinical atherosclerosis, independently of traditional cardiovascular risk factors. A longer duration of breastfeeding may have a beneficial effect on subclinical atherosclerosis later in life.